Flouting of Maxims in Finding Dory Movie - Widiantari, Ni Made Ayu; Pratiwi, Desak Putu Eka; Sekolastika, Made Perdana (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-July, 2022)
This research aims to describe the types of maxims that are flouted in Finding Dory , to reveal and explain the strategies used by the main characters to flout maxims in Finding Dory , and to describe the functions of maxim flouting done by the main characters in Finding Dory . The study concerns with the flouting maxims that occur in main characters utterances in reaching their goal in Finding Dory movie, a movie which uses under sea universe as the main theme of the story. The study aims at analyzing the types of flouting maxims, and motivation of flouted maxim which frequently used in a conversation between main characters other characters in Finding Dory movie and the reason of applying that particular type of flouting maxims, and motivation to giving information the interlocutor in the utterances. This study uses qualitative method to conduct a clear and well organized description about the problems which is identified. Descriptive study in textual analysis is applied to elaborate the flouting maxims which occur in Finding Dory movie. The data were taken from the script and analyzed by applying Cooperative Principle theory proposed by Grice (1975). The study concludes that the flouting maxim of relation and quantity is mostly applied by the main characters to giving the information the interlocutor but the information is irrelevant.